Employment and human capital investment intentions among recent refugees in Germany - Peter Haan; Martin Kroh; Kent Troutman (Deutsches Institut für Wirtschaftsforschung (DIW), 2017)
Motivations to participate in the labour market as well as to invest in labour market skills are crucial forthe successful integration of refugees. In this paper we use a unique dataset - the IAB-BAMF-SOEPRefugee Survey, which is a representative longitudinal study of all refugees reported on administrativerecords in Germany - and analyse which determinants and characteristics are correlated with highmotivation and intention to participate in the labour market. We find that overall men have a strongintention to work and to invest in human capital. The result for women is different: among women,having children, lack of German language skills, and having no previous work experience significantlyand consistently correlate with lower expectations and intentions of future economic integration.Furthermore, we find a significant relationship between the degree of traditional or patriarchal views ofwomen's societal roles, and our corresponding outcomes of interest.
Keywords: F22; J22; J24; 330